Strategic Agility and Intellectual Capital towards Organizational Performance in Higher Education Institutions - Abd Rahman Ahmad; Mohammed Alzoraiki (Communications of International Proceedings, 2021)
Strategic agility has a key role in institutions attainment of optimum success but the lack of conceptual framework in literature that sheds light on the relationship between strategic agility and intellectual capital, and their impact on the performance of institutions in higher education leaves the topic under a grey area. Therefore, the present paper primarily aims to develop a framework, within which intellectual capital has a mediating role on the relationship between strategic agility and institutional performance. There is a dire need to investigate strategic agility in Malaysian Higher Education Institutions (HEIs), particularly in the face of the current Covid-19 pandemic, for the purpose of developing resources and capabilities and using them to achieve positive organizational performance.
Keywords: Strategic Agility; Intellectual Capital; Organization Performance; And Higher Education Institutions.